Evaluation of Microstructures of ZnO Nanocrystals Fabricated by Different Methods - Oral, Ahmet Yavuz (Polish Acad Sciences Inst Physics, 2013)
ZnO nanocrystalline powders were fabricated by the solutions prepared by dissolving zinc acetate in isopropyl alcohol. Ethanolamine was used to enhance the solubility of acetates. Nanocrystalline powders were obtained either from the dried gels or precipitated solutions followed by calcination at different temperatures. Microstructural characterization of the powders showed that both morphology and the crystallite size of powders significantly altered based on the fabrication method and the calcination temperature. DOI: 10.12693/APhysPolA.123.169
2nd International Congress on Advances in Applied Physics and Materials Science (APMAS) -- APR 26-29, 2012 -- Antalya, TURKEY
Keywords: Powder